2011
DOI: 10.1177/0022034511402206
|View full text |Cite
|
Sign up to set email alerts
|

Differential TRPV1 and TRPV2 Channel Expression in Dental Pulp

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. ABSTRACTHypersensitivity to thermal and mechanical stimuli can occur in painful pulpitis. To explore the neuroanatomical basis of heat and mechanical sensitivity, we evaluated expression of TRPV1 (heat) and TRPV2 (heat/mechanical) channels in the cell bodies and terminal arborizations of neurons that innervate the dental pulp (DP) and periodontal tissues (PDL). We report that ~50% of trigeminal gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 34 publications
4
75
0
1
Order By: Relevance
“…The extent of the proportion of IB4-positive pulpal afferents in retrogradely labeled pulpal afferents is controversial. In rats, labeling of IB4 in TG sections showed that less than 5% of retrogradely labeled dental afferents are IB4-positive (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011). In contrast, the percentages of IB4-positive pulpal afferents in cultured dental afferents were as high as 75% (Park et al, 2006;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of the proportion of IB4-positive pulpal afferents in retrogradely labeled pulpal afferents is controversial. In rats, labeling of IB4 in TG sections showed that less than 5% of retrogradely labeled dental afferents are IB4-positive (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011). In contrast, the percentages of IB4-positive pulpal afferents in cultured dental afferents were as high as 75% (Park et al, 2006;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the roles of these afferents in tooth pain remain to be elucidated. Most of the TRPV1-expressing pulpal afferents are CGRP-positive (Gibbs et al, 2011), suggesting the possibility that some peptidergic afferents are transmitting thermal pain. Tooth injury induces branching of peptidergic afferent terminals and release of CGRP (Byers and Närhi, 1999), suggesting the possible involvement of peptidergic pulpal afferents in mechanical nociception as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the expression level of TRPV2 is higher in labeled dental afferent neurons (37%) than in unlabeled trigeminal ganglion neurons (14%). Indeed, half of the neurons that innervate the periodontal ligament express TRPV2 (Gibbs et al, 2011).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…TRPV1 et TRPV2 sont principalement exprimés par les fibres myélinisées. Néanmoins, une forte proportion de fibres nerveuses IB4 positives exprime TRPV1 [7]. Le schéma d'expression de ces récepteurs contribue à définir une signature neurochimique particulière pour chaque type d'afférences impliqué dans l'innervation pulpaire.…”
Section: Diversité Des Afférences Dentaires Primairesunclassified